UNLEASHING LEARNING POTENTIALS AMONG PASSIVE STUDENTS - Mohd Nur Fitri Mohd Salim; Asmahanim Haji Mohamad Yusuf; Irma Ahmad; Mohamad Safwat Ashahri Mohd Salim (Journal of Islamic, Social, Economics and Development, 2020)
There is a significant relationship between students’ passiveness in the classroom with the level of their motivation in a learning environment. This heavily influences the outcome of a particular learning goal, since motivation has a significant impact to students’ level of effort to learn. This paper discussed on the importance for educators to explore the needs of passive students in order to ensure that these students will not be left behind in achieving the learning goals in the classroom. This includes the need to evaluate the students learning preferences, understanding the reasons for them to be passive and the roles of teachers in facilitating these students to achieve their full learning potentials. This includes the efforts that are needed from the teacher to experiment with various teaching and classroom management skills, since it is found that teachers who are able to cater to the needs of passive students were able to produce positive outcomes and nurture better learning habits among passive students